PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN ROTTE BAKERY BUKIT BARISAN PEKANBARU - Marcelino, Dafa; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The purpose of this study was to determine the effect of service quality, product quality and pricing on customer satisfaction at Rotte Bakery Bukit Barisan Pekanbaru. This research is a quantitative study with a sample of 160 respondents. This data source is obtained from secondary data and primary data. The study used a questionnaire as a data collection technique using the accidental sampling method, which is a sampling technique based on chance. The analysis methods used in this study are validity test, reliability test, heteroscedasticity classical assumption test, multiple linear analysis, t test, F test and coefficient of determination (R2) analysis. The results of this study are Service Quality (X1) has a significant effect on Customer Satisfaction (Y), Product Quality (X2) has a significant effect on Customer Satisfaction (Y), Pricing (X3) has a significant effect on Customer Satisfaction (Y), and Service Quality, Product Quality and Pricing have a significant effect on Customer Satisfaction. Keywords: Service Quality, Product Quality, Pricing, Consumer Satisfaction